(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1989)
Records kept in the royal burgh of Selkirk concerning the regulation of staple foodstuffs, markets, weights and measures and craft guilds show the importance of co-operation and self-regulation within the trade community. A R